Analysis of the Availability of Information for Aspiring Multinational Companies in South Africa - Modisane , Mpho; Mah, Gisele; Shah, Paul (International Review of Management and Marketing, 2023)
Aspiring multinational companies have very few guidelines on how to expand their businesses beyond South Africa, unlike established multinational companies. The plight of aspiring multinational companies finding business opportunities beyond national borders highlights the importance of properly understanding the international business environment. The purpose of this study is to evaluate the availability of information for aspiring multinational companies. The study employs a quantitative method, and the population is 196 managers of aspiring multinational companies in South Africa. The primary data for this study was obtained by administering questionnaires to managers of aspiring multinational companies in South Africa. The findings of the study revealed that companies that have been in operation for less than three years have a challenge accessing the information to successfully penetrate multinational business markets. These challenges experienced by the newer aspiring multinational companies emanate from the fact that they do not have any guidelines on what needs to be in place and from where they can get the information. It is recommended that aspiring multinational corporations in South Africa access information on running multinational businesses, especially information on the regulatory and economic environment such as international laws, local spending, and the public environment.